Beyond common explanations: Incorporating digital technology and culture into classrooms in México (Revista Peruana de Investigación Educativa, 2014)
More and more teachers in Mexico are expected to use digital technologies in their classrooms. However, little guidance is provided for them to transition from pencil and paper practices to the screen. This article argues that that teachers’ use of digital technology (or lack thereof) is a social construction where multiple processes -the realities of their workplace, their understanding of digital technologies and the Internet, and their longstanding beliefs about teaching and learning- coincide to shape their classroom practices. The author builds her analysis of three teachers learning to use technology in their classrooms in México City on socio cultural theory, most notably notions concerning social interaction and practice. She illustrates teachers’ heterogeneous responses to this new professional demand. She concludes that specific classroom uses of technology are the result of teachers’ particular articulation of the multiple relationships and obstacles encountered in their workplace.
Keywords: technology; teacher’s practice; digital culture; high school; Mexico